Education for Management: New Directions and New Challenges - Farland, Dalton E. Mc (Academy of Management Journal, 1959)
Describes developments in management education and interprets their impact on the teaching of management at the university level. Decline of the functional concept; Growth in scientific disciplines; Impact of changes on patterns of administration and on the field of management.